Cognition and autonomy in dependent elderly people. - Álvarez-Hernández, Joaquín; Aguilar-Parra, José Manuel; Mercader-Rubio, Isabel (Anales de Psicología / Annals of Psychology, 2012)
The aim of this work has been to relate the cognitive impairment in elderly people to the preservation of those daily life activities that turn out to be more complex and that provide them with a state of advanced autonomy. The sample has been composed of 472 patients (163 males and 309 women), at ages understood between 60 and 102 years. The design corresponds to the correlational descriptive study of evaluative investigation. Results. The results obtained have been analyzed though the answers to the instruments of evaluation SPMQ (Pfeiffer) and ESENP, contemplating the mental condition of the patients and verifying their managing of the daily life activities, as well as the relation between both factors taking into account differences depending on the ages and sexes. Conclusions. The information registered in this study shows us the relation that exists between cognitive deterioration and the personal autonomy in elderly people what allows to define accurately the real needs of the future population as for social community services, being able to use them with the intention of optimizing and extending the above mentioned services.